PERILAKU GENERASI MUSLIM Z DI APLIKASI TIKTOK - Desta Fitriana; Johannes, Johannes; Ekasari, Novita (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
The purpose of this study is to explain the influence of fashion trends, promotions, and online shopping preferences on the purchasing decisions of Muslimah fashion products on TikTok. This research employs a quantitative approach with a non-probability sampling method due to the unknown population size, involving a sample of 96 respondents. The data used is primary data obtained from a digital questionnaire via Google Forms with a 5-point Likert scale. The distribution of this questionnaire was carried out via WhatsApp and Instagram.. The data analysis method used the Partial Least Square (PLS) based Structural Equation Model (SEM) 4.1. The results indicate that fashion trends, promotions, and online shopping preferences significantly influence the purchasing decisions of Muslimah fashion products on TikTok in the Generation Z era. This study provides strategic recommendations for Muslimah fashion business actors to continue innovating in product design, optimizing promotions, and ensuring comfort and enhancing user experience in online shopping to attract and retain consumers.